1995
DOI: 10.1111/j.1365-2958.1995.tb02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional expression of bacteriophage PK1E‐encoded endoneuraminidase Endo NE

Abstract: Homopolymeric alpha-2,8-linked sialic acid (PSA) has been found as a capsular component of sepsis- and meningitis-causing bacterial pathogens, and on eukaryotic cells as a post-translational modification of the neural cell adhesion molecule (NCAM). The polysaccharide is specifically recognized and degraded by a phage-encoded enzyme, the endo-N-acetylneuraminidase E (Endo NE). Endo NE therefore has become a valuable tool in the study of bacterial pathogenesis and eukaryotic morphogenesis. In this report we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…2). In all samples, the specificity of the PSA signal was shown by EndoNE digestion, which degrades PSA and abolishes binding of mAb 735 (36). Expression levels of the recombinant epitope-tagged proteins were monitored by Western blot analysis using the anti-FLAG mAb M5 and the anti-HA mAb 12CA5.…”
Section: Figmentioning
confidence: 99%
“…2). In all samples, the specificity of the PSA signal was shown by EndoNE digestion, which degrades PSA and abolishes binding of mAb 735 (36). Expression levels of the recombinant epitope-tagged proteins were monitored by Western blot analysis using the anti-FLAG mAb M5 and the anti-HA mAb 12CA5.…”
Section: Figmentioning
confidence: 99%
“…Gradient gels were prepared with ProSieve 50 gel solution (BioWhittaker) and run in Tris/Tricine electrode buffer according to the manufacturer's instructions for 12% resolving and 3% stacking gels. For Western blot analysis proteins were blotted onto nitrocellulose membranes (Schleicher & Schuell), and blots were developed as described (18). For detection of His 6 -tagged proteins Penta-His antibody (Qiagen) was used at a concentration of 1 g/ml.…”
Section: Fig 2 Proteolytic Cleavage Of Endosialidasesmentioning
confidence: 99%
“…Cloning of endoNE revealed that the gene encodes a 90-kDa protein, whereas for the purified phage-borne and the recombinantly expressed endoNE an apparent molecular mass between 74 and 76 kDa was observed (8,18,19), indicating post-translational processing. In contrast, no discrepancy be-* This work was supported by Deutsche Forschungsgemeinschaft Grant GE 801/3-3 and by the Fonds der Chemischen Industrie.…”
mentioning
confidence: 99%
See 2 more Smart Citations